Evaluating the implementation and use of the regional cancer plan in Western Sweden through concept mapping. (21st December 2018) - Smith, Frida; Gunnarsdóttir, Katrín Ásta; Genell, Anna; McLinden, Daniel; Vaughn, Lisa; Garelius, Hege; Nilsson-Ehle, Herman; Lönqvist, Ulf; Björk-Eriksson, Thomas
Abstract: Quality problem or issue: Within healthcare, policy documents are often used to strategically standardize, streamline or change how general health issues are managed for a specific patient group or treatment. Despite significant effort in developing policy and strategic planning documents, these may not have the intended impact and their value has long been questioned by practitioners. Choice of solution: To identify barriers and affordances for the implementation and use of a strategic plan for cancer care in the Western Sweden Healthcare Region, we used Concept Mapping; a participatory mixed method approach to inquiry consisting of both qualitative and quantitative tasks intended to elicit and integrate the diverse perspectives of multiple stakeholders. Implementation: The study was carried out between April and October 2017 and consisted of several sequential data collection steps: idea generation, sorting and rating ideas for importance and feasibility. Stakeholders from different levels and professions in cancercare participated, but the number varied in the separate steps of data collection: idea generation ( n = 112), sorting ( n = 16) and rating ( n = 38). Evaluation: A concept map visualized seven areas that stakeholders throughout the cancer-care process considered necessary to address in order to enable the implementation of the plan. Skills provision was considered the most important cluster but also rated as least feasible. A consistent theme emerged that information, or lack thereof, might be a barrier for the plan being put into action to a greater extent in the cancer-care units. Nine actionable ideas rated highly on both importance and feasibility were presented as a go-zone. Lessons learned: Our results suggest that efforts might be better spent on ensuring information about and accessibility to strategic documents throughout the organization, rather than frequently updating them or producing new ones. Having sufficient skills provision seems to be the prerequisite for successful implementation.